2021
DOI: 10.26417/129zga77p
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Some Fluids Extracts of Indigenous Wild Cherry Fruits

Abstract: The paper presents un study regarding the comparative total antioxidant capacity of some fluids extracts of the soluble lipid compounds of Cerasus avium (L.) Moench. syn. Prunus avium (L.) var. sylvestris Ser fruits, popular named wild cherry, species undertaken aiming at exploiting the nutrient profiles and promoting the further development of these indigen phytopharmaceutical resources. For analysis, the photo-chemiluminescence method, ACL procedure, Analytik Jena AG, by comparing with the standard Trolox® s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The calibration curve (Figure 4) was calculated using a series of standard solutions containing 0.5, 1.0, 2.0, 3.0 nM Trolox (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid), a vitamin E derivative. Determinations were performed in triplicate and were expressed as nM Trolox equivalents (TE)/μL sample, respectively mg (TE)/100 g d.w. sample [25][26][27]. All modules were instrumented with ChemStation HPLC data-acquiring software.…”
Section: Antioxidant Activity Analysismentioning
confidence: 99%
“…The calibration curve (Figure 4) was calculated using a series of standard solutions containing 0.5, 1.0, 2.0, 3.0 nM Trolox (6-hydroxy-2,5,7,8-tetramethylchroman-2-carboxylic acid), a vitamin E derivative. Determinations were performed in triplicate and were expressed as nM Trolox equivalents (TE)/μL sample, respectively mg (TE)/100 g d.w. sample [25][26][27]. All modules were instrumented with ChemStation HPLC data-acquiring software.…”
Section: Antioxidant Activity Analysismentioning
confidence: 99%
“…Some epidemiological and interventional studies have demonstrated a positive correlation between the consumption of polyphenolic-rich fruits and reduced chronic diseases [ 12 ]. Medicinal plants have been used since ancient times to treat or prevent various diseases, and researchers are now observing them with increased attention [ 4 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%